Mitigasi bencana gempa bumi berbasis kearifan lokal masyarakat rote Kabupaten Rote Ndao Provinsi Nusa Tenggara Timur - Jonas Thene (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
This study aims to find local knowledge society Rote Ndao face earthquakes. The method used is a qualitative method that is focused on extracting information about the knowledge and experience of communities in Rote Ndao Rote Ndao in the face of the earthquake disaster. This research was conducted in two places, namely in the Village Lakamola and Village Mukebuku Eastern District of Rote Rote Ndao. In this study involved 20 people as informers; which is determined by a snowball and accompanied by their willingness to be involved in this research. The following results. First, Rote Ndao people have no knowledge of earthquakes, they just have myths about earthquakes. Myth for them is to bring citizens at the core of its life or the true identity; thanks to the myth, every citizen will be able to meet with his own distinctive, while at the same time they will also meet with fellow humans are also the universe, and the Divine. Myth inspire people to maintain and develop a harmonious living together in a community setting: between macro-cosmos, micro-cosmos and Invisible Invisible. Secondly, experience Rote Ndao society in the face of the earthquake disaster, they use local wisdom, screaming when the quake lasted ami nai ai o ... They were happy because of their belief that the current year will bring soil fertility and agricultural crops will be abundant. Senasiblah feeling that drives people to be aware of the meaning of the collectivity as social beings. In this case, the earthquake that devastated people's lives ago has sowed seeds of solidarity, and solidarity. Third, Rote Ndao people have no knowledge of earthquake disaster mitigation, his experience is to use local wisdom.Keywords: earthquake, mitigation, local knowledge, community Rote Ndao. http://dx.doi.org/10.17977/um022v1i22016p102